Video game plotline tester eaudiobook - Atamanov, Michael (Dark Herbalist, 2017)
Would you be prepared to work for free? How would you like to bust your hump for a large corporation sixty-plus hours a week without a wage or a single day off for the vague promise of some mysterious perks in the distant future? You'd refuse point blank, wouldn't you? But what if the job in question was playing a state-of-the-art fantasy MMORPG game? And what if this was the only thing you're really good at? Especially considering that your in-game partner is someone really special to you—and this person already lives a virtual life? Knowing all this, would you consider the mysterious future bonus worth your while?